Resonant grating of magnetodielectric resonance nanospheres - Kozar, A. I. (ХНУРЭ, 2017)
he design method, based on integral equations of macroscopic electromagnetics, is proposed for studying the electromagnetic waves scattering by the limited resonance grating, made of small resonance magnetodielectric spheres, located in the magnetodielectric environment. The analytical investigations of fields scattered by the resonance grating are presented.The advancement of nanotechnologies is related with the use of metamaterials whose structure discreteness and associated resonance phenomena are of primary importance. Interaction between electromagnetic radiation and metacrystals at the resonance domain is complicated and insufficiently studied. Methods for electromagnetic simulation of the phenomena in crystal lattices metacrystals are developed in order to help studying them. На основе интегральных уравнений макроскопической электродинамики предложен расчетный метод изучения рассеяния электромагнитных волн ограниченной резонансной решеткой из малых резонансных магнитодиэлектрических сфер, находящейся во внешней магнитодиэлектрической среде. Представлено аналитическое исследование рассеянных полей резонансной решеткой.
Keywords: nanotechnologies; electromagnetic radiation; metacrystals